METAPHOR EXPRESSION IN FALL FOR YOU SONG LYRICS - Faidah Yusuf; Andi Reski Amelia (Elite : English and Literature Journal, 2018)
The purpose of this article is to analyze the type of metaphor and analyze the meaning in the lyrics of the song "Fall for You" the method uses a qualitative approach because the data used in the form of song lyrics. Document analysis is applied to find the connotation meaning contained in the song lyrics, the messages contained in the song, as well as the contribution of the connotations to the messages in the song. The writers collected data by downloading songs along with lyrics, reading song lyrics, and creating phrases that contain metaphorical meanings. Then the writers analyzed the data by identifying the meaning, find the intent contained in the song, and connect with the types of metapor. The results of the discussion data show that there are. There are seven types of meaning in the data are: conceptual, connotative, social, affective, reflective, collocative and thematic meaning. The song uses metaphor and other types of meaning to embellish the song and to convey the implicit message in the song. The messages contained in the song are mostly persuasive. metaphors found in song lyrics have an important role in creating certain feelings and conveying messages.Keywords: Metaphor, Meaning, Song lyricsABSTRAKTujuan dari artikel ini adalah untuk menganalisa jenis metafora dan menganalisa makna dalam lirik lagu "Fall for You". Metodenya menggunakan pendekatan kualitatif karena data yang digunakan dalam bentuk lirik lagu. Analisis dokumen diaplikasikan untuk menemukan makna konotasi yang terkandung dalam lirik lagu, pesan yang terkandung dalam lagu, serta kontribusi konotasi terhadap pesan dalam lagu tersebut. Peneliti mengumpulkan data dengan mendownload lagu beserta liriknya, membaca lirik lagu, dan membuat ungkapan yang mengandung makna metafora. Kemudian para peneliti menganalisis data dengan mengidentifikasi maknanya, menemukan maksud yang terkandung dalam lagu, dan terhubung dengan jenis-jenis metapor. Hasil dari data diskusi menunjukkan bahwa ada. Ada tujuh jenis makna dalam data tersebut yaitu: makna konseptual, konotatif, sosial, afektif, reflektif, kolektif dan tematik. Lagu tersebut menggunakan metafora dan jenis makna lainnya untuk memperindah lagu dan menyampaikan pesan implisit dalam lagu tersebut. Pesan yang terkandung dalam lagu sebagian besar bersifat persuasif. Metafora yang ditemukan dalam lirik lagu memiliki peran penting dalam menciptakan perasaan dan menyampaikan pesan.Kata kunci: Metafora, Makna, lirik lagu